2016
DOI: 10.1103/physreva.94.013834
|View full text |Cite
|
Sign up to set email alerts
|

Resonance fluorescence spectrum of aΛ-type quantum emitter close to a metallic nanoparticle

Abstract: We theoretically study the resonance fluorescence spectrum of a three-level quantum emitter coupled to a spherical metallic nanoparticle. We consider the case that the quantum emitter is driven by a single laser field along one of the optical transitions. We show that the development of the spectrum depends on the relative orientation of the dipole moments of the optical transitions in relation to the metal nanoparticle. In addition, we demonstrate that the location and width of the peaks in the spectrum are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Localized surface plasmons, plasma oscillations occurring at the surface of finite metallic nanostructures, can alter drastically the spontaneous emission properties of nearby quantum emitters (QEs) [1,2]. A large number of theoretical works have shown that the spontaneous emission spectra [3][4][5][6] or the resonance fluorescence spectra and the corresponding statistical properties of emitted light [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] of QEs in the vicinity of plasmonic nanostructures, like metallic or metal-dielectric nanostructures, are dramatically different from the case where the QEs are placed in an isotropic dielectric or free-space vacuum. These findings are also supported by experimental studies [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Localized surface plasmons, plasma oscillations occurring at the surface of finite metallic nanostructures, can alter drastically the spontaneous emission properties of nearby quantum emitters (QEs) [1,2]. A large number of theoretical works have shown that the spontaneous emission spectra [3][4][5][6] or the resonance fluorescence spectra and the corresponding statistical properties of emitted light [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] of QEs in the vicinity of plasmonic nanostructures, like metallic or metal-dielectric nanostructures, are dramatically different from the case where the QEs are placed in an isotropic dielectric or free-space vacuum. These findings are also supported by experimental studies [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The metal nanoparticles (MNPs) can enhance the nonlinear optical response due to the large local field enhancement induced near the surface and control the optical properties of quantum emitters near the MNPs [ 13 , 14 , 15 ]. Moreover, plasmonic excitations can respond within femtoseconds enabling ultrafast processing of optical signal [ 16 ], with high sensitivity to the size and the shape of the MNPs as well as the dielectric properties of the metal and surrounding medium [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 1 we present the modification in the quantum dot's spontaneous decay rate for two different quantum dot's electric dipole directions, along the x-axis (γ x ) and along the z-axis (γ z ), as a function of distance d. The obtained behavior is typical, see, for example, refs. [4][5][6]9,10]. Both decay rates are enhanced for small distances between the quantum dot and the metal nanoparticle, but as this distance increases the decay rate corresponding to the electric dipole direction along the x-axis decreases monotonically and the value of the decay rate remains larger than the spontaneous decay rate in the absence of the metallic nanoparticle γ 0 .…”
Section: Resultsmentioning
confidence: 95%